The role of radiotherapy for patients with primary tracheal carcinoma: two case reports of tracheal carina squamous cell carcinoma and literature review - Chang, Xiaojing; Tian, Zhesen; Zhao, Yalei; Ge, Xiaohui; Li, Feng; Yang, Yu; Liu, Huizhi (Frontiers in Oncology, 2025)
Primary tracheal carcinoma is a rare malignant tumor; its optimal treatment strategy is not yet formally proven. Surgery, especially complete surgical excision, is often considered as the first-line treatment, and chemotherapy has been reported ineffective. There is a growing body of evidence suggesting that radiotherapy may offer better local control and improve survival outcomes for cases of incomplete excision, questionable surgical margins, or unresectable lesions. However, the effect, total dose, and fraction dose of radiotherapy remain controversial. We report two cases of primary tracheal squamous cell carcinoma at the tracheal carina: a 74-year-old man with an unresectable tracheal carcinoma at the carina and a 55-year-old woman with a tracheal tumor. Both of them were treated with radical radiotherapy, demonstrating satisfactory local control. Finally, we review the current progress of radiotherapy in primary tracheal carcinoma.